Implementasi Customer Relationship Management pada Telemarketing Pelanggan Tidak Aktif di Lotte Grosir Bandung - Yulia Dasmiyanti; Firman Yudhanegara (INDO PUBLISHING, 2026)
This study analyzes the implementation of Customer Relationship Management (CRM) in telemarketing activities for inactive customers at Lotte Grosir Bandung using a descriptive qualitative approach. Data were collected through direct observation, documentation, and analysis of communication results during the internship program. The findings show that telemarketing activities play a role in identifying factors that contribute to customer inactivity, including price differences with competitors, less strategic store location, and limited product availability. The data recording and classification process also helps the company group customers based on their activity level and reasons for inactivity. The study concludes that CRM implementation through telemarketing and customer data management supports customer reactivation efforts, although it is still limited by low customer response rates and incomplete data.